Radon and thoron exhalation rate, emanation factor and radioactivity risks of building materials of the Iberian Peninsula - Frutos-Puerto, Samuel; Pinilla-Gil, Eduardo; Andrade, Eva; Reis, Mário; Madruga, María José; Miró Rodríguez, Conrado (PeerJ, 2020)
Radon (222Rn) and thoron (220Rn) are radioactive gases emanating from geological materials. Inhalation of these gases is closely related to an increase in the probability of lung cancer if the levels are high. The majority of studies focus on radon, and the thoron is normally ignored because of its short half-life (55.6 s). However, thoron decay products can also cause a significant increase in dose. In buildings with high radon levels, the main mechanism for entry of radon is pressure-driven flow of soil gas through cracks in the floor. Both radon and thoron can also be released from building materials to the indoor atmosphere. In this work, we study the radon and thoron exhalation and emanation properties of an extended variety of common building materials manufactured in the Iberian Peninsula (Portugal and Spain) but exported and used in all countries of the world. Radon and thoron emission from samples collected in the closed chamber was measured by an active method that uses a continuous radon/thoron monitor. The correlations between exhalation rates of these gases and their parent nuclide exhalation (radium/thorium) concentrations were examined. Finally, indoor radon and thoron and the annual effective dose were calculated from radon/thoron concentrations in the closed chamber. Zircon is the material with the highest concentration values of 226Ra and 232Th and the exhalation and emanation rates. Also in the case of zircon and some granites, the annual effective dose was higher than the annual exposure limit for the general public of 1 mSv y−1, recommended by the European regulations.
Keywords: Radon; Thoron; Building materials; Exhalation rate; Annual effective dose